(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
The feeling of being out-of-place from dressing differently from others is prevalent in Japanese individuals. However, previous studies have not objectively assessed this out-of-place feeling using physiological indices. Therefore, this study aimed to compare out-of-place feelings in Japanese individuals measured using questionnaires as subjective assessments and electroencephalography, R-R interval of heartbeats, and number of blinks as objective assessments. The results indicated that the participants felt out-of-place because of the differences in clothing and the recipient of the letter they wrote to as the task. The out-of-place feeling had a significantly negative correlation with alpha waves and a significantly positive correlation with beta waves. The more the participants felt out-of-place, the more uncomfortable they were when the collaborator entered or left the room wearing different clothes. The more their beta waves activated when they wrote a letter to their supervisor than when they wrote to children. The decrease in middle-alpha waves suggested that the participants were uncomfortable when they were the only people in a different outfit.